A mechanical property evaluation of Ti6Al4V cellular lattice structures fabricated by selective laser melting - M. Z., Azir; W. S. W., Harun; K., Kadirgama (IOP Publishing, 2020)
Cellular structures are similarly identified as lattice structures or foam structures which are commonly constructed of ligaments. Cellular structures exist widely in nature, such as the coral, honeycomb, and the natural bones. Cellular structures are also manufactured and used in various applications such as honeycomb bumper structures and truss bridge. Ti6Al4V is one of the most commonly used titanium alloy and is applied in a wide range of application where low density very good corrosion resistance are necessary such as direct manufacturing of part and prototypes for racing and aerospace industry, biomechanical application such as implants and prosthesis, marine application, chemical industry, and gas turbine. This paper investigates the mechanical properties of Ti6Al4V lattice structures fabricated by additive manufacturing, also known as 3D printing. The samples are fabricated by selective laser melting (SLM) using titanium alloy (TI6Al4V). Four factors were selected to determine its influence on the Young's modulus and compressive strength, which is strut size, strut shape, unit cell size, and porosity. All the samples categorize to six groups by its design volume porosity obtained from CAD file. Solidwork design software was used in this study. The influence was shown in a comparison graph. Detailed characterizations of compression test were conducted and reported. The built structures have a Young's modulus ranging between 0.01 and 1.84 Gpa. Porosity was realized to play an important role in determining the Young's modulus and compressive strength.